Study of V-notch fatigue strength based on affected depth approach - Youssef, Marwa; Nasr, Anouar (Comptes Rendus. Mécanique)
In this work, the Affected Depth (AD) approach is employed to estimate the high cycle fatigue limit of AISI 416 steel weakened by notches. This approach is based on a critical depth parameter identified from the analysis of the stress distribution around the defect. Elasto-plastic finite element calculations have been performed to determine the stress field close to the notch. Where the notch is modeled by a discontinuity of matter (void) characterised by: (i) a notch depth and (ii) a notch tip radius. The Crossland equivalent stress is employed to compute the stress surrounding the notch of a V-notched material submitted to fully reversed torsion and tension loadings. The experimental results of notched materials, used for model validation, are obtained from the literature. In the first part of the paper, Fatigue Limit diagram is simulated by assessing the fatigue limits to validate the AD model for notched components. The prediction of the fatigue strength is consistent with the experimental investigation taken from the literature, and it provides interesting results. In the second part of the paper, two points are treated: (i) The effect of the notch acuity on the plastic strain and the stress concentration. It allows testing the capability of the AD approach to describe the fatigue behavior of the V-notched components. (ii) The impact of the notch tip radius on the affected depth parameter of notched low carbon steel.